Answer:
C
Step-by-step explanation:
I think it is C. Sorry if I'm wrong.
Given
f(x)= -3x - 5
g(x)= 4x - 2
Find
(f - g)(x)
substitute the f and g values in (f - g)
(f - g)(x)= -3x - 5 - (4x - 2)
change the signs in parentheses because there is a negative sign in front of the parentheses
(f - g)(x)= -3x - 5 - 4x + 2
combine like terms
(f - g)(x)= -7x - 3
ANSWER: (f - g)(x)= -7x - 3
Hope this helps! :)
I dont know if this is right but here u goo
EXPLANATION:
Let the smaller no. be x.
Therefore, The bigger no. = x+12
x + 12 + x = 84
=> 2x = 84-12
=> x = 72/2
=> x = 36
ANSWER: The two numbers are (36+12) 48 & 36
Hope it helps u!